John Philoponus on physical place - Papachristou, Ioannis (Ancient and medieval philosophy., 2021)
This book examines the place of physical bodies, a major topic of natural philosophy that has occupied philosophers since antiquity. Aristotle?s conceptions of place (topos) and the void (kenon), as expounded in the 'Physics', were systematically repudiated by John Philoponus (ca. 485-570) in his philosophical commentary on that work. The primary philosophical concern of the present study is the in-depth investigation of the concept of place established by Philoponus, putting forward the claim that the latter offers satisfactory solutions to problems raised by Aristotle and the Aristotelian tradition regarding the nature of place. Philoponus? account proposes a specific physical model of how physical bodies exist and move in place, and regards place as an intrinsic reality of the physical cosmos. Due to exactly this model, his account may be considered as strictly pertaining to the study of physics, thereby constituting a remarkable episode in the history of philosophy and science.